2018
DOI: 10.1016/j.jacl.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Task-sharing interventions for cardiovascular risk reduction and lipid outcomes in low- and middle-income countries: A systematic review and meta-analysis

Abstract: BackgroundOne of the potential strategies to improve health care delivery in understaffed low- and middle-income countries (LMICs) is task sharing, where specific tasks are transferred from more qualified health care cadre to a lesser trained cadre. Dyslipidemia is a major risk factor for cardiovascular disease but often it is not managed appropriately.ObjectiveWe conducted a systematic review with the objective to identify and evaluate the effect of task sharing interventions on dyslipidemia in LMICs.MethodsP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
(148 reference statements)
0
20
0
Order By: Relevance
“…We developed a search strategy based on a previous review 15 and modified the terms according to the database. We searched PubMed, Embase, Cochrane Library, and CINAHL with terms related to cardiovascular disease, task sharing, and LMICs (appendix pp 46–53).…”
Section: Methodsmentioning
confidence: 99%
“…We developed a search strategy based on a previous review 15 and modified the terms according to the database. We searched PubMed, Embase, Cochrane Library, and CINAHL with terms related to cardiovascular disease, task sharing, and LMICs (appendix pp 46–53).…”
Section: Methodsmentioning
confidence: 99%
“…(1) the motivation underlying task-sharing for abortion services; (2) their own roles in advocating for task-sharing; (3) factors that facilitated task-sharing in abortion care in Ghana; (4) barriers to tasksharing in abortion care; and (5) opportunities to task-share beyond the midwife.…”
Section: Resultsmentioning
confidence: 99%
“…1 Tasksharing can make more efficient use of the human resources currently available by reallocating tasks among healthcare workers; for example, enabling lay and midlevel healthcare professionals such as nurses, midwives, medical doctors, and community health workers to provide clinical tasks and procedures that would otherwise be restricted to higher-level cadres. 2 Ghana has expanded nurses' roles or, in some cases, has provided nurses with additional training to perform tasks that were previously ascribed to only physicians. These are generally midlevel cadres defined by the Ghana Health Service as: "the person trained to support the highly trained health professionals and can hold the fort in the absence of the professional".…”
Section: Introductionmentioning
confidence: 99%
“…Community-based cardiovascular health interventions in vulnerable populations has shown that the interventions aimed at decreasing blood pressure are the most promising and behavior change interventions are the most challenging [ 22 , 23 ]. Task-shifting interventions were also proven to be effective in lowering the low-density lipoprotein cholesterol (LDL) and total cholesterol [ 24 ]. In another review, significant reduction in the mean blood pressure and glycated haemoglobin levels were seen in task-shifting interventions for the CVD risk reduction in LMICs [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Task-shifting interventions were also proven to be effective in lowering the low-density lipoprotein cholesterol (LDL) and total cholesterol [ 24 ]. In another review, significant reduction in the mean blood pressure and glycated haemoglobin levels were seen in task-shifting interventions for the CVD risk reduction in LMICs [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%